Dinamika Pemasaran Tiktok Shop: Peran Live Streaming, Content Marketing, dan Online Customer Review dalam Meningkatkan Keputusan Pembelian Konsumen - Irdiana, Sukma; Robustin, Tri Palupi; Putri, Nur Latifa Isnaini (Jurnal Ilmiah Global Education, 2025)
TikTok launched the TikTok Shop feature to continue its mission to make its users happy by providing easy shopping without having to switch applications. The purpose of this research is to analyze the influence of content marketing, live streaming and online customer reviews on purchasing decisions for fashion products on Shopee. This type of research is explanatory research with a quantitative approach. The population in this research is all consumers who have purchased fashion products on TikTok Shop. The data source used is primary data by distributing questionnaires. The research method is the probability sampling method which determines the sample with a purposive sampling technique. The sample was selected according to the guidelines of Hair et al (2010) which resulted in 135 respondents. The data analysis technique used in this research is multiple linear regression analysis using the SPSS statistical tool version 21. The results of the research show that Live streaming has a positive effect on purchasing decisions for fashion products. Content Marketing has a positive effect on purchasing decisions for fashion products. Online customer reviews have a positive but insignificant effect on purchasing decisions for fashion products. This research can provide in-depth insight into the factors that influence consumer purchasing decisions on TikTok Shop, especially for fashion products. These findings can be an important reference for business people, marketers, and researchers to develop more effective marketing strategies in the context of e-commerce.